An observational study «FOLLITROPIN» comparing the efficacy of follitropin alpha biosimilar: the real-world data - D. P. Kamilova; M. M. Ovchinnikova; E. Sh. Ablyaeva; M. M. Leviashvili; N. S. Stuleva; E. V. Broitman; M. A. Ganikhina; E. N. Mayasina; L. F. Iskhakova; K. Yu. Boyarskiy; E. N. Ovsyannikova; Z. B. Barakhoeva; et al. (Акушерство, гинекология и репродукция)
Introduction. The efficacy and safety of biosimilar follitropin alpha have been demonstrated in randomized blinded prospective clinical trials of phases I and III. Unfortunately, there is a gap between the clinical trials and real clinical practice data. The real-world patient data helps to create an evidence-based background for successful implementation of medicine at everyday practice in a nonselected population.Aim: to investigate the efficacy of follitropin alpha biosimilar therapy (Primapur®) in nonselected real-world population.Materials and Methods. A retrospective observational anonymized cohort study of follitropin alpha biosimilar (Primapur®) as a pre-filled pen injector with a dose adjustment of 5 IU, aimed to investigate its efficacy and safety in a nonselected population with indications to assisted reproductive technologies (ART) was carried out. The ovarian stimulation (OS) protocols included: monotherapy protocols with using only Primapur®; mixed protocols (recombinant and urinary-derived gonadotropins); short protocols with using antagonists of gonadotropin-releasing hormone (GnRH) and long protocols with GnRH agonists. The stimulation protocols were analyzed with Primapur® application for at least 5 days.Results. The overall clinical efficacy of ovarian stimulation cycles (N = 5484) was: oocytes retrieved - 9.5 ± 7.2, mature (MII) - 6.8 ± 6.6, fertilized (2PN) - 6.1 ± 5.8, clinical pregnancy per ET (PR) - 38.4 %. Mixed gonadotropin protocols (N = 2625) vs. monotherapy with Primapur® (N = 2859): oocytes retrieved - 8.6 ± 6.8 vs. 10.3 ± 7.4 (p < 0.001), mature (MII) - 6.7 ± 6.2 vs. 7.7 ± 6.9 (p < 0.001), fertilized (2PN) - 5.8 ± 5.2 vs. 7.2 ± 6.2 (p < 0.001). There were statistically significant differences between oocyte yields in mixed vs. monotherapy protocols due to subgroup differences, including age, body mass index (BMI) and IVF/ICSI attempts. No statistically significant differences were found for PR: 39.3 % vs. 37.6 % (p = 0.314). Monotherapy protocols with GnRH antagonist OS (N = 2183) vs. GnRH agonist (N = 676) revealed: oocytes retrieved - 10.5 ± 7.5 vs. 9.6 ± 7.0 (p = 0.032), mature (MII) - 7.6 ± 6.9 vs. 6.7 ± 5.7 (p < 0.001), fertilized (2PN) - 7.3 ± 6.3 vs. 5.7 ± 5.0 (p < 0.001). There were statistically significant differences between BMI and IVF/ICSI attempts. No statistically significant differences were found for PR: 37.9 % vs. 35.9 % (p = 0.482). All medicines were well tolerated and no serious adverse reactions were reported.Conclusion. This was the largest retrospective observational study conducted in the field of fertility in Russia and involved 5484 ovarian stimulation protocols at 35 IVF clinics. The obtained results demonstrated similar clinical efficacy for follitropin alpha biosimilar Primapur® in different OS protocols in real clinical practice.